Agromorphological Diversity of Sorghum Accessions Collected in North-West Benin - Hafiz A. Salami; Marius Guedou; Guirguissou Mamoudou Alidou; Donatien Ahissou; Yannick S. C. Gogan; Pascal Koi; Barnabé Kindohoun; Maurice Hodonou; Haziz Sina (Indian Journal of Genetics and Plant Breeding, 2026)

Bonobo (Pan paniscus) Density and Distribution in Central Africa's Largest Rainforest Reserve: Long-term Survey Data Show Pitfalls in Methodological Approaches and Call for Vigilance - Mattia Bessone; Hjalmar S. Kühl; Ilka Herbinger; Gottfried Hohmann; Kouamé Paul N’Goran; Papy Asanzi; Stephen Blake; Michel Basele; Martin Bofeko; Nono Bondjengo; Pitshou Wangongo Bondo; Rigobert Booto; et al. (International Journal of Primatology, 2025)
Conservation measures require accurate estimates of density and abundance and population trend assessments. The bonobo ( Pan paniscus ) is considered Endangered in the IUCN Red List. This classification assumes that available population data are representative. However, with only 30% of the bonobo’s historic geographical range surveyed, reliable information is needed to assess the species' population status. Here, we use information from 13 surveys conducted between 2002 and 2018 in an area of 42,000 km 2 , representing ~27% of bonobo-suitable habitat: Salonga National Park and its corridor, Democratic Republic of the Congo (DRC). Using 8310 km of reconnaissance and transect walks and 27,045 days of camera trapping, we: (1) provide updated estimates of bonobo population density and distribution (42,000 km 2 ; ~5,000 km 2 of which, to the best of our knowledge, have not been surveyed before by scientists), (2) assess population trends (15,758 km 2 ; 2002–2008 vs 2012–2018), (3) compare estimates obtained with different methods, and (4) assess the factors driving bonobo density and distribution. Although we detected a non-significant population decline, our study suggests that Salonga is a bonobo stronghold, with a population ranging between 8244 and 18,308 mature individuals (density: 0.31 individuals/km 2 ). Standing crop nest counts returned non-significantly lower density estimates than camera trap distance sampling. Nest count-estimates were higher in areas with Marantaceae understorey and those farther away from rivers, while camera trap-estimates were higher in areas with lower human presence. Regardless of the method, bonobos were rarer in proximity to villages. They occurred more often in areas of dense forest cover and in proximity to ranger posts. Our results point towards a declining bonobo population in Salonga, but do not provide sufficient evidence to confirm this statistically. Consequently, the continued monitoring of the bonobo population and preservation of the integrity of Salonga, considering its biological and cultural heritage, will be crucial in the preservation of this stronghold of wild bonobos.

Sialic acids cleavage induced by elastin-derived peptides impairs the interaction between insulin and its receptor in adipocytes 3T3-L1 - Alexandre Guillot; Kevin Toussaint; Lucrece Ebersold; Hassan ElBtaouri; Emilie Thiebault; Tarik Issad; Franck Peiretti; Pascal Maurice; Hervé Sartelet; Amar Bennasroune; Laurent Martiny; Manuel Dauchez; et al. (Journal of Physiology and Biochemistry, 2024)

Lactosylceramide induced by elastin-derived peptides decreases adipocyte differentiation - Thinhinane Hocine; Sebastien Blaise; Cathy Hachet; Alexandre Guillot; Herve Sartelet; Pascal Maurice; Amar Bennasroune; Laurent Martiny; Laurent Duca; Beatrice Romier-Crouzet; Hassan EL Btaouri (Journal of Physiology and Biochemistry, 2020)

Human proximity and habitat fragmentation are key drivers of the rangewide bonobo distribution - Jena R. Hickey; Janet Nackoney; Nathan P. Nibbelink; Stephen Blake; Aime Bonyenge; Sally Coxe; Jef Dupain; Maurice Emetshu; Takeshi Furuichi; Falk Grossmann; Patrick Guislain; John Hart; et al. (Biodiversity and Conservation, 2013)

Chloroplast DNA phylogeography suggests a West African centre of origin for the baobab, Adansonia digitata L. (Bombacoideae, Malvaceae) - JEAN‐MICHEL LEONG POCK TSY; ROSELYNE LUMARET; DIANA MAYNE; ABDALLAHI OULD MOHAMED VALL; YAHIA I. M. ABUTABA; MAURICE SAGNA; SOAHARIN’NY ONY RAKOTONDRALAMBO RAOSETA; PASCAL DANTHU (Molecular Ecology, 2009)
The African baobab ( Adansonia digitata L.) is an emblematic, culturally important, and physically huge tropical tree species whose natural geographical distribution comprises most of tropical Africa, but also small patches of southern Arabia, and several Atlantic and Indian Ocean islands surrounding the African continent, notably including Madagascar. We analysed the polymerase chain reaction–restriction fragment length polymorphism of five chloroplast DNA fragments obtained from 344 individuals of A. digitata collected from 74 populations covering the entire extant distribution range of the species. Our goal was to reconstruct the phylogeographical history of the species and, if possible, to identify its centre of origin, which has been a subject of controversy for many decades. We identified five haplotypes whose distribution is clearly geographically structured. Using several species of Adansonia and of closely related genera as outgroups, the haplotypes showed a clear phylogeographical pattern of three groups. Two are phylogenetically related to the outgroup taxa, and are distributed in West Africa. The third group is substantially more differentiated genetically from outgroup species, and it corresponds to southern and eastern Africa, Arabia and the Indian Ocean islands, including Madagascar. According to our results, the tetraploid A. digitata , or its diploid progenitor, probably originated in West Africa and migrated subsequently throughout the tropical parts of that continent, and beyond, by natural and human‐mediated terrestrial and overseas dispersal.

The platelet receptor for type III collagen (TIIICBP) is present in platelet membrane lipid microdomains (rafts) - Pascal Maurice; Ludovic Waeckel; Viviane Pires; Pascal Sonnet; Monique Lemesle; Brigitte Arbeille; Jany Vassy; Jacques Rochette; Chantal Legrand; Françoise Fauvel-Lafève (Histochemistry and Cell Biology, 2006)

The sigma1 (?1) receptor activation is a key step for the reactivation of cocaine conditioned place preference by drug priming - Pascal Romieu; Johann Meunier; Dborah Garcia; Nadia Zozime; Rmi Martin-Fardon; WayneD. Bowen; Tangui Maurice (Psychopharmacology, 2004)

The antidepressant-like effect induced by the sigma1 (σ1) receptor agonist igmesine involves modulation of intracellular calcium mobilization - Alexandre Urani; Pascal Romieu; Elodie Portales-Casamar; François J. Roman; Tangui Maurice (Psychopharmacology, 2002)